Acessibilidade e inclusão de estudantes com deficiência no Ensino Superior: uma análise discursiva crítica do Jornal de Folha de Acessibilidade UFC-Inclui - Gomes, Reubher César Rodrigues (2023)
This dissertation aims to analyze, based on the theoretical and methodological assumptions of Critical Discourse Analysis, the discursive representations about accessibility and the inclusion of students with disabilities at the Universidade Federal do Ceará, based on texts published in the Folha Acessibilidade newspaper. It is justified because it is inserted in the context of social and institutional change through which the Brazilian public Higher Education has been going through with the policy of inclusion of students with disabilities. In fact, in 2005, the Ministry of Education (MEC) created the Programa Incluir, aimed at cooperating in the elaboration and consolidation of accessibility nuclei in public universities. The UFC has already received resources in the first Call for Proposals, in 2006. Thus, it is necessary to understand the discourses that shape this process. The theoretical basis is based on Disability Studies (OLIVER, 1994; BARNES, 2012; UPIAS, 1976; MARTINS, 2006), which conceive disability as a social oppression, i.e., as a limitation resulting from socially imposed barriers. The concepts of inclusion and accessibility arise from this conception, and are constituted as a way to eliminate barriers and ensure the autonomy of the disabled public (LEITÃO, 2014). The linguistic foundation is based on Critical Discourse Analysis (CDA), with emphasis on the Representational Meaning, i.e., the ways in which different discourses are articulated and materialized in texts, in order to represent social phenomena (FAICLOUGH, 2003, 2016; CHOULIARAKI; FAICLOUGH, 1999). For ADC, the social sphere and discourse are mutually constituted, which is why the investigation of the process of inclusion and accessibility through discourse is productive. The methodology is qualitative intepretativist (MAGALHÃES; MARTINS; RESENDE, 2017), and documentary. We elected as analytical material the texts published in the newspaper Folha Acessibilidade, material produced by the Accessibility Department with a view to disseminating the disabled universe in the context of the UFC. This newspaper was published between the years 2014 and 2017, containing 08 (eight) editions in all. Thus, the universe of this research consists of the eight editions, and the sample chosen for analysis comprises 17 texts. For the analysis of the texts, the categories of intertextuality, interdiscursivity, modality, representation of social actors were chosen. The linguistic-discursive analyses of the texts showed the existence of a discursive conflict between the concepts of exclusion and inclusion, so that institutional inclusion is represented under the aegis of the segregation of the disabled public in their own medical institutions. Furthermore, the analysis of the voices and interdiscursive relations showed a connection to biomedical discourses of care and attention, generating a semantic conflict between the concepts of inclusion and care. We also observed a systematic silencing of the voices of people with disabilities to the detriment of the publicity of the Secretariat of Accessibility as the body authorized to speak for these people. We conclude that the representations are linked to discourses of care, silencing and institutional oppression, which can generate the perpetuation of veiled oppression under the semantic banner of inclusion.